ANALISIS KINERJA KEUANGAN BANK MILIK PEMERINTAH INDONESIA - Gianni, Shelli Elsa; saiful, saiful; Aprila, Nila (JURNAL FAIRNESS, 2020)
Central government-owned bank is a bank owned by the government / state in which its activities of collecting funds mainly accept deposits in the form of demand deposits and deposits and in the effort to provide short-term credit and fund collection mainly as savings and then to deposit their funds in valuable paper. Whereas a regional government-owned bank is a bank that collects funds primarily accepting deposits in the form of medium-term and long-term deposits and or paper deposits. The aim of this research is to analyze and find out the differences in financial performance between banks owned by the central government and the banks owned by the regional government using financial ratios. The data used in this study are secondary data obtained from the financial statements of banks owned by the central government and banks owned by local governments. The research sample was chosen based on the purposive sampling method of all listed banking companies on the Indonesia Stock Exchange (IDX) and the Financial Services Authority website. Samples obtained were 28 companies with 112 observations. The results showed that there were significant differences between the financial performance of central government-owned banks and regional government-owned banks from Loan to Deposit Ratio (CAR), Capital Adequacy Ratio (CAR), Non Performing Loans (NPLs), Return On Assets (ROA) and Operational Fees on Operational Revenues (BOPO). Whereas in the ratio of Net Interest Margin (NIM) the financial performance of banks owned by the central government and banks owned by regional governments there was no significant difference.